In Conversation: Two Community Foundations in Dialogue About Their Equ itable Evaluation Framework™ Practice - Brandt, Madeline; Casey, Kelly; Callan, Jean-Marie; Hicks-Rivera, Joel; Leonard, Kim; Nguyen, Madeline; Ragusa, Elena Tamanas; Stancil, Cierra; Salmond, Kimberlee; Seel, Becky; Szczerbacki, Kate (The Foundation Review, 2023)
This conversation between staff at the Oregon Community Foundation and the Hartford Foundation for Public Giving shares how we are infusing the Equitable Evaluation Framework™ into our practice as we aim to be less extractive, shift power, and honor all ways of knowing and being as valid. In sharing this conversation, we want to pull the curtain ba ck and offer a behind-the-scenes view into the conversations, realitie s, and challenges involved in doing this kind of work. We sat down tog ether for 90 minutes on a Wednesday afternoon, and the following is a rough transcript of our time together. The intention is not for the ar ticle to be an exemplar, but instead to demonstrate the complexities i n applying the EEF in real settings and the patience and persistence i t takes for organizational (and personal) transformation. We started o ur conversation with these questions: 1) Why is applying the EEF princ iples and challenging orthodoxies important for your practice? How is this approach helping us show up authentically? 2) What does applying EEF principles/ challenging orthodoxies look and feel like for you now ? How are you infusing it in your work? Where does it feel easier or h arder, and why? 3) Where do you hope to go from here? What does applyi ng the EEF look like for you in the future? Along the way, the convers ation gives the opportunity to see that our practice and takeaways as Equitable Evaluation partners and practitioners vary depending on who we are and our role in the foundation. We speak to the many ways that this work can “look” and the ways that the journey of each foundation is shaped by its starting place, mission, and culture. We hope readers will see themselves within the dialogue and understand that there are many ways to start, engage in, and further this work.